(untitled) (Islas, 2024)
Introduction: This article analyzes the cultural and historical theme in the correspondence of José Manuel Carbonell y Rivero, found in the Francisco de Paula Coronado Bibliographic Collection at the Universidad Central «Marta Abreu» de Las Villas. Methods: The analysis is quantitative, employing content analysis and bibliographic documentation as methods. It relies on inductive-deductive and historical-logical principles to provide textual and extratextual data of interest in the reading of the letters. Results: The main subjects of the letters are discussed, including literary disputes, poetry recitals, the founding of the Cuban Academy of Language, the motives associated with the death of Juan Clemente Zenea, the historical significance of the figure of Pedro Santicilia, and the request for the safeguarding of the mortal remains of José María Heredia by the Veterans of the Independence of eastern Cuba. The study involves emitters Carlos Loveira, Juan Manuel Planas, Dulce María Loynaz, Bonifacio Byrne, Antonio Valverde, Ramiro Guerra, and Ramón Prida. Conclusions: The weight of the correspondence in shaping relevant issues of national identity is acknowledged.